PERAN BIAYA LINGKUNGAN DAN PROFITABILITAS TERHADAP NILAI PERUSAHAAN DENGAN KINERJA LINGKUNGAN SEBAGAI VARIABEL MEDIASI (Studi Empiris pada Perusahaan-Perusahan Manufaktur yang Terdaftar di Bursa Efek Indonesia 2021-2024) - Muhammad Mikael Putra Herawantho; Etna Nur Afri Yuyetta (Diponegoro Journal of Accounting, 2025)
This study aims to examine the role of Environmental Costs and Profitability on Firm Value with Environmental Performance as a mediating variable of manufacturing companies listed on the Indonesia Stock Exchange in 2021-2024. This study refers to stakeholder theory and legitimacy theory. The population used in this study consists of manufacturing companies listed on the Indonesia Stock Exchange (IDX) from 2021 to 2024. Purposive sampling was used in selecting the research sample, resulting in 120 research samples for four consecutive years (2021–2024).The analysis results show that Environmental Costs have a positive and significant effect on Environmental Performance, and Profitability also has a positive and significant effect on Environmental Performance. Additionally, it was found that Environmental Costs do not have a significant direct effect on Firm Value. Meanwhile, Profitability has a positive and significant effect on Firm Value, and Environmental Performance also has a positive and significant effect on Firm Value. This study also found that Environmental Performance significantly mediates the relationship between Environmental Costs and Firm Value, as well as significantly mediates the relationship between Profitability and Firm Value.